Compression moulding of hybrid carbon fibre composites for structural applications - Corbridge, David Michael (2018)
Automotive manufacturers are receiving pressure from customers and regulators to reduce emissions. Reducing the weight of the vehicle through the use of carbon fibre is seen as one of these mechanisms. The challenge is to develop suitable manufacturing processes that can offer appropriate cycle times to meet demand and deliver materials with adequate mechanical properties for structural applications. Compression moulding of discontinuous fibre moulding compounds with local continuous fibre inserts provide better production rates and part complexity compared to the autoclave components and higher performances than injection moulding. However, combining a unidirectional carbon fibre (UD) material with a random short fibre orientation sheet moulding compound (SMC) that flows heterogeneously will lead to degradation in the properties of the continuous reinforcement. This work aims to demonstrate a hybrid of continuous and discontinuous fibre compounds in a single moulding operation with increased stiffness and determine if the surface distortion of the reinforcement can be used to predict local stiffness.